Strength training for endurance athletes: Theory to practice - Bazyler, C. D.; Abbott, H. A.; Bellon, C. R.; Taber, C. B.; Stone, M. H. (Strength and Conditioning Journal, 2015)
The purpose of this review is twofold: to elucidate the utility of resistance training for endurance athletes, and provide the practitioner with evidenced-based periodization strategies for concurrent strength and endurance training in athletic populations Both low-intensity exercise endurance (liee) and high-intensity exercise endurance (hiee) have been shown to improve as a result of maximal, high force, low velocity (hflv) and explosive, low-force, high-velocity strength training. Hflv strength training is recommended Initially to develop a neuromuscular base for endurance athletes with limited strength training experience. A sequenced approach to strength training involving phases of strengthendurance, basic strength, strength, and power will provide further enhancements In liee and hiee for highlevel endurance athletes.